FLEXURAL BEHAVIOUR OF RECTANGULAR CFST BEAMS STRENGTHENED WITH INNOVATIVE STEEL PLATE REINFORCEMENTS - Nurulhuda Shafiqah, Obeng; Abdul Azim, Abdullah (School of Engineering, Taylor’s University, 2022)
Concrete-filled steel tube (CFST) is an excellent composite member in resisting bending. However, CFST beams experience reduced flexural stiffness due to concrete tensile cracking at early loading stage, which hinders its full potential. This study proposes an innovative method to improve the flexural performance of CFST beams by embedding longitudinal steel plates into the tensile zone of the concrete core. The objectives of this study are to investigate the effectiveness of the proposed method and evaluate the influence of the quantity, height, and thickness of the steel plates. A total of eight rectangular CFST specimens were experimentally tested under pure bending. All specimens are embedded with steel plates except one, which acts as a control. Outcomes from the experimental tests reveal that the use of embedded steel plates can enhance the flexural performance of the CFST beams. The specimens with embedded steel plates develop better moment-deflection relationship and demonstrate higher strength capacity and stiffness compared to the control specimen. Also, the performance of the CFST beams improves with increasing the quantity, height, and thickness of the steel plates. An improvement of 17.4% in the moment capacity can be observed when embedding the CFST beam with just one steel plate and further optimized up to 43.4% by adding three embedded steel plates. Furthermore, it was found that increasing the thickness of the steel plates is the most effective, followed by quantity and height. Additionally, the theoretical ultimate moment was calculated based on the plastic stress model. The theoretical ultimate moment was around 5% lower than the experimental result, with a standard deviation of 0.025. Therefore, it is recommended for determining the ultimate capacity of the CFST beams with embedded steel plates. Overall, the proposed method of embedding steel plates works efficiently in enhancing the flexural performance of the CFST beams. © School of Engineering, Taylor’s University.